2013
DOI: 10.2147/itt.s31428
|View full text |Cite
|
Sign up to set email alerts
|

Anti-amyloid-beta to tau-based immunization: developments in immunotherapy for Alzheimer's disease

Abstract: Immunotherapy might provide an effective treatment for Alzheimer disease (AD). A unique feature of AD immunotherapies is that an immune response against a self antigen needs to be elicited without causing adverse autoimmune reactions. Current research is focussed on two possible targets in this regard: One is the inhibition of accumulation and deposition of Amyloid beta 1-42 (Aβ42), which is one of the major peptides found in senile plaques and the second target is hyperphosphorylated tau, which forms neurofib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 93 publications
0
18
1
Order By: Relevance
“…Results from mice receiving passive Aβ immunization had shown that anti-Aβ antibodies enter the brain and are found in regions with high amyloid concentrations; the ability to enter the brain changes with age and might depend also on features specific to the antibodies (Banks et al, 2007; Bard et al, 2000). The antibody amounts found in aged DNA-immunized mice (mean 53 μg/mL plasma) were higher than the antibody levels, we had found earlier in transgenic APP mice (2.9 μg/mL plasma) and inwhich we found a substantial reduction in plaque load (50%) and total Aβ42 levels (41%) in brain from the immunized mice compared with control mice (Lambracht-Washington and Rosenberg, 2013b; Qu et al, 2006, 2007). …”
Section: Discussioncontrasting
confidence: 57%
“…Results from mice receiving passive Aβ immunization had shown that anti-Aβ antibodies enter the brain and are found in regions with high amyloid concentrations; the ability to enter the brain changes with age and might depend also on features specific to the antibodies (Banks et al, 2007; Bard et al, 2000). The antibody amounts found in aged DNA-immunized mice (mean 53 μg/mL plasma) were higher than the antibody levels, we had found earlier in transgenic APP mice (2.9 μg/mL plasma) and inwhich we found a substantial reduction in plaque load (50%) and total Aβ42 levels (41%) in brain from the immunized mice compared with control mice (Lambracht-Washington and Rosenberg, 2013b; Qu et al, 2006, 2007). …”
Section: Discussioncontrasting
confidence: 57%
“…Some of the trials had to be interrupted, either because of detrimental side-effects or lack of the evident efficacy. Those studies were recently in [135,136]. Other approaches, which are also being discussed as possible treatments of AD, are a) BACE-1 inhibitors, and b) tau-immunotherapy, reviewed in [136,137].…”
Section: Polyphenolsmentioning
confidence: 99%
“…Those studies were recently in [135,136]. Other approaches, which are also being discussed as possible treatments of AD, are a) BACE-1 inhibitors, and b) tau-immunotherapy, reviewed in [136,137]. However, their application to human patients still remains unknown.…”
Section: Polyphenolsmentioning
confidence: 99%
“…Passive immunization has also been assessed in clinical trials (Lambracht-Washington and Rosenberg 2013;Wilcock and Colton 2008). This can, in theory, negate the effects of immune senescence observed in elderly AD patients and avoid T cell-mediated encephalitis.…”
Section: Protective Role For T Cells In Ad; Immunizationmentioning
confidence: 99%